2015
DOI: 10.1128/jvi.03531-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus-Induced Caspase-Dependent Enlargement of Nuclear Pores Promotes Nuclear Export of Viral Ribonucleoprotein Complexes

Abstract: Influenza A viruses (IAV) replicate their segmented RNA genome in the nucleus of infected cells and utilize caspase-dependent nucleocytoplasmic export mechanisms to transport newly formed ribonucleoprotein complexes (RNPs) to the site of infectious virion release at the plasma membrane. In this study, we obtained evidence that apoptotic caspase activation in IAV-infected cells is associated with the degradation of the nucleoporin Nup153, an integral subunit of the nuclear pore complex. Transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 51 publications
3
68
0
Order By: Relevance
“…ER stress is involved in the pathogenesis of IAV (46), and BIK initiates ER Ca 21 release prior to the activation of effector caspases (11). In response to ER stress, GRP78 dissociates from the luminal domain of these sensors, leading to their activation (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER stress is involved in the pathogenesis of IAV (46), and BIK initiates ER Ca 21 release prior to the activation of effector caspases (11). In response to ER stress, GRP78 dissociates from the luminal domain of these sensors, leading to their activation (47).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have shown that Bik mediates activation of caspases in cells infected with Epstein-Barr virus (20). Recent studies have shown that IAVinduced caspase activation causes a widening of nuclear pores to facilitate passive transport of viral ribonucleic protein (RNP) to ensure efficient production of infectious virus progeny (21). Inhibitors of host cell proteases have been used effectively to reduce viral replication and treat infection, such as in the case of HIV-1 infection (22).…”
mentioning
confidence: 99%
“…Indeed, nucleuslocalized GFP via an NLS leaks into the cytosol and proteins up to 140 kDa enter the nucleus of apoptotic cells, while a 580-kDa GFP-tagged b-galactosidase fusion protein remains in the cytoplasm and 4',6-diamidino-2-phenylindole-stained DNA stays nuclear [119]. Enlargement of the NPC facilitates diffusion of medium-sized proteins through the NPC [123], including that of executioner caspases 3, 6, and 7 (50-70 kDa). Redistribution of several transport factors in the nucleus and cytoplasm is observed along with an accumulation of nuclear mRNAs [124].…”
Section: Nuclear Pore and Transportmentioning
confidence: 99%
“…In an attempt to close this gap of knowledge between the previous observation and the current understanding of IAV replication we performed the present study and now provide evidence that Verapamil profoundly affects the replication and transcription activity of the viral RNA-dependent RNA polymerase (RdRp), resulting in reduced expression of viral proteins and, consequently, reduced production of virus progeny. Furthermore, we demonstrate that Verapamil interferes with the virus-induced activation of the transcription factor NF-κB, known to be involved in the expression of pro-apoptotic factors and subsequent apoptotic caspase-3 activation, the latter shown previously to promote viral RNP export [15,16]. Taken together, the data suggest that Verapamil has diverse effects on both virus and host cell functions that collectively result in strongly reduced IAV replication in vitro.…”
Section: Introductionmentioning
confidence: 55%
“…Additionally, it was demonstrated that activation of the apoptotic Caspase 3 is also important for efficient IV propagation [39] as IV-induced Caspase-dependent enlargement of nuclear pores promotes nuclear export of the viral RNPs [16]. Current understanding therefore proposes a model that connects the observed events, e.g.…”
Section: Discussionmentioning
confidence: 99%